Amorphous film and preparation method and application thereof
By using the combination of Al, Si and C in the amorphous film and preparing it by magnetron sputtering method, the problem of insufficient toughness of amorphous films is solved, and the AlSiC amorphous with high strength, high hardness and high toughness is achieved The film extends its service life.
Patent Information
- Application Number
- CN202411666729.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Due to insufficient toughness, amorphous films are prone to brittle fracture, shortening their service life.
Three atoms, Al, Si and C, are arranged in disorderly into an AlSiC amorphous film, and are prepared by magnetron sputtering method to control the components and thickness to achieve high strength, high hardness and high toughness.
It realizes the integration of strength and toughness of amorphous films, enhances its protective effect, and extends its service life.
Smart Images

Figure CN119465026A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material technology, and in particular to an amorphous film and a preparation method and application thereof. Background Art
[0002] Amorphous films are composed of disordered atoms. This disorder causes its internal bonding structure to be long-range disordered and short-range ordered, which makes the amorphous film have high hardness and strength. However, it also brings the problem of low toughness. In practical applications, when the amorphous film is subjected to load, it is prone to brittle fracture due to its insufficient toughness, which shortens its service life. Summary of the invention
[0003] Based on this, it is necessary to provide an amorphous film and a preparation method and application thereof to address the above problems. The amorphous film has high strength, high hardness and high toughness, and has a longer service life when used as a surface protection material.
[0004] An amorphous film is an AlSiC amorphous film composed of Al, Si and C.
[0005] In one embodiment, the amorphous film is composed of 20.6%-22.8% Al, 33.1%-34.7% Si, and 42.5%-46.3% C in terms of atomic fraction.
[0006] In one embodiment, the thickness of the amorphous film is 800 nm-2 μm.
[0007] A method for preparing the amorphous film comprises the following steps:
[0008] Providing target materials;
[0009] The amorphous film is deposited on the substrate by magnetron sputtering.
[0010] In one embodiment, the target material is selected from a composite material of Al and SiC.
[0011] In one of the embodiments, in the composite material of Al and SiC, the mass ratio of Al to SiC is 3:7.
[0012] In one embodiment, in the magnetron sputtering step, the RF power applied during deposition is 500W-600W.
[0013] In one embodiment, in the magnetron sputtering step, the deposition gas pressure is 0.32Pa-0.36Pa.
[0014] In one embodiment, in the magnetron sputtering step, the deposition time is 7200 seconds to 18000 seconds.
[0015] The amorphous film is used as a surface protective material.
[0016] The present invention adopts AlSiC amorphous film formed by disorderly arranging three atoms of Al, Si and C, so that the AlSiC amorphous film has high strength, high hardness and high toughness, and the amorphous film realizes strong and tough integration. Furthermore, when the AlSiC amorphous film of the present invention is used as a surface protection material, the protection effect is good and the service life is longer.
[0017] At the same time, the present invention adopts a magnetron sputtering method to prepare an AlSiC amorphous film, and the deposition rate is stable. The deposited AlSiC amorphous film has uniform composition, dense structure, few defects, good bonding with the substrate, and strong adhesion. Furthermore, when the AlSiC amorphous film of the present invention is used as a surface protection material and is formed on the surface of a to-be-protected component by a magnetron sputtering method, the AlSiC amorphous film has a good bonding effect with the to-be-protected component and is not easy to peel off. The AlSiC amorphous film has high strength, high hardness and high toughness, good protection effect, and long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is an AFM surface morphology image of the AlSiC amorphous film prepared in Example 1 of the present invention;
[0020] Figure 2 This is a low magnification TEM image of the AlSiC amorphous film prepared in Example 2 of the present invention;
[0021] Figure 3 TEM selected area electron diffraction pattern and high resolution image of the AlSiC amorphous film prepared in Example 2 of the present invention, wherein a is the TEM selected area electron diffraction pattern and b is the high resolution image;
[0022] Figure 4 The loading-unloading curve of the AlSiC amorphous film nanoindentation prepared in Example 2 of the present invention;
[0023] Figure 5 This is a surface morphology of the AlSiC amorphous film prepared in Example 2 of the present invention after nano-scratching. DETAILED DESCRIPTION
[0024] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0026] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0027] The amorphous film provided by the present invention is an AlSiC amorphous film, which is composed of Al, Si and C. It can be understood that the three atoms of Al, Si and C in the AlSiC amorphous film are arranged disorderly. The present invention makes the amorphous film have high strength, high hardness and high toughness through the selection of the components of the amorphous film, and realizes strong and tough integration. Furthermore, when the AlSiC amorphous film of the present invention is used as a surface protection material, the protection effect is good and the service life is longer.
[0028] Preferably, in terms of atomic fraction, the amorphous film is composed of 20.6%-22.8% Al, 33.1%-34.7% Si and 42.5%-46.3% C. For example, the amorphous film is composed of 20.6% Al, 33.1% Si and 46.3% C. Alternatively, the amorphous film is composed of 21.0% Al, 33.5% Si and 45.5% C. Alternatively, the amorphous film is composed of 21.0% Al, 33.5% Si and 45.5% C. The film is composed of 21.5% Al, 34.0% Si and 44.5% C, or the amorphous film is composed of 22.0% Al, 34.5% Si and 43.5% C, or the amorphous film is composed of 22.8% Al, 34.7% Si and 42.5% C. With this arrangement, the amorphous film can have high strength and high hardness while better taking into account toughness, thereby achieving strong and tough integration.
[0029] Preferably, the thickness of the amorphous film is 800nm-2μm, for example, 800nm, 900nm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, or a range consisting of any two of these values.
[0030] The preparation methods of amorphous films mainly include physical vapor deposition, liquid phase quenching, reaction, etc. Among them, when the magnetron sputtering method is used, the deposition rate is stable, and the deposited amorphous film has uniform composition, dense structure, few defects, good bonding with the substrate, and strong adhesion. Therefore, the present invention also provides a method for preparing the amorphous film by magnetron sputtering, comprising the following steps:
[0031] Providing target materials;
[0032] The amorphous film is deposited on the substrate by magnetron sputtering.
[0033] Different target materials are selected, and the effects of the amorphous films deposited are different. In the present invention, the target material is preferably selected from a composite material of Al and SiC. At the same time, by controlling the mass ratio of Al and SiC in the target material, the atomic ratio of Al, Si and C in the obtained AlSiC amorphous film can be regulated. Preferably, in the composite material of Al and SiC, the mass ratio of Al and SiC is 3:7, so that in combination with the deposition process conditions, an AlSiC amorphous film composed of 20.6%-22.8% Al, 33.1%-34.7% Si and 42.5%-46.3% C can be obtained.
[0034] In the magnetron sputtering step, some process conditions will affect the density and energy of the deposited particles, and thus affect the deposition rate and the microstructure of the film. Preferably, the RF power applied during deposition in the present invention is 500W-600W, for example, 500W, 550W, 600W, or a range consisting of any two of these values, and the deposition gas pressure is 0.32Pa-0.36Pa, for example, 0.32Pa, 0.33Pa, 0.34Pa, 0.35Pa, 0.36Pa, or a range consisting of any two of these values, to obtain an amorphous film with better quality.
[0035] Furthermore, in the magnetron sputtering step, the deposition time is preferably 7200 seconds to 18000 seconds, so that an amorphous film of a desired thickness can be obtained by controlling the deposition time.
[0036] It can be understood that in the magnetron sputtering method of the present invention, there is no limitation on the substrate, which can be a silicon substrate or other metal substrates. Before depositing the amorphous film, it is preferred to vacuum etch the substrate and sputter clean the target to remove contaminants on the surface of the substrate and the target.
[0037] Since the amorphous film of the present invention has high strength, high hardness and high toughness, the present invention also uses the amorphous film as a surface protection material, which can not only provide better protection effect but also extend the service life.
[0038] It can be understood that when the amorphous film of the present invention is used as a surface protection material, the part to be protected can be directly used as a substrate for magnetron sputtering, so that the AlSiC amorphous film is directly formed on the surface of the part to be protected. In this way, not only the AlSiC amorphous film has a good bonding effect with the part to be protected and is not easy to peel off, but also the AlSiC amorphous film has high strength, high hardness and high toughness, good protection effect and long service life.
[0039] Hereinafter, the amorphous film and its preparation method and application will be further described through the following specific examples.
[0040] Example 1
[0041] The single crystal silicon substrate is fixed on the base plate, and the automatic sample feeder sends the base plate into the magnetron sputtering coating chamber, and the vacuum is evacuated to make the vacuum degree of the vacuum chamber reach 5×10 -4 Pa, argon gas was introduced into the vacuum chamber with a flow rate of 110 sccm, and etching was first performed at a power of 200 W for 30 s, and then at a power of 300 W for 200 s.
[0042] A composite material of Al and SiC (Al: 30 wt.%, SiC: 70 wt.%) was provided as a target material, and a radio frequency power source was used to clean the surface of the target material at a power of 200 W for 30 seconds.
[0043] Then, an AlSiC amorphous film is deposited on a single crystal silicon substrate by a magnetron sputtering method. In the magnetron sputtering step, a radio frequency power supply is used, the power is 600W, the deposition pressure is 0.34Pa, the substrate speed is 10r / min, and the deposition time is 7200 seconds. After the deposition process is completed, the automatic sampling device takes the substrate out of the vacuum chamber to obtain an AlSiC amorphous film with a thickness of 800nm, wherein the atomic proportion of Al in the AlSiC amorphous film is 22.0%, the atomic proportion of Si is 34.5%, and the atomic proportion of C is 43.5%.
[0044] like Figure 1 As shown in the figure, it is the AFM surface morphology of the AlSiC amorphous film prepared in this embodiment. Figure 1 It can be seen that the surface of the AlSiC amorphous film is smooth and the roughness is 0.9 nm.
[0045] In addition, after testing, the hardness value of the AlSiC amorphous film prepared in this embodiment is 16.64 GPa, the Young's modulus is 192.18 GPa, and the nano scratch load reaches 100 mN without cracks.
[0046] Example 2
[0047] The single crystal silicon substrate is fixed on the base plate, and the automatic sample feeder sends the base plate into the magnetron sputtering coating chamber, and the vacuum is evacuated to make the vacuum degree of the vacuum chamber reach 5×10 -4 Pa, argon gas was introduced into the vacuum chamber with a flow rate of 110 sccm, and etching was first performed at a power of 200 W for 30 s, and then at a power of 300 W for 200 s.
[0048] A composite material of Al and SiC (Al: 30 wt.%, SiC: 70 wt.%) was provided as a target material, and a radio frequency power source was used to clean the surface of the target material at a power of 200 W for 30 seconds.
[0049] Then, an AlSiC amorphous film was deposited on a single crystal silicon substrate by a magnetron sputtering method. In the magnetron sputtering step, a radio frequency power supply was used with a power of 600 W, a deposition pressure of 0.34 Pa, a substrate rotation speed of 10 r / min, and a deposition time of 18,000 seconds. After the deposition process, an automatic sampling device took the substrate out of the vacuum chamber to obtain an AlSiC amorphous film with a thickness of 2 μm, wherein the atomic proportion of Al in the AlSiC amorphous film was 20.6%, the atomic proportion of Si was 33.1%, and the atomic proportion of C was 46.3%.
[0050] A Pt protective layer was formed on the surface of the AlSiC amorphous film prepared in this embodiment, and then a TEM test was performed. Figure 2This is a low-magnification TEM image, from top to bottom, it is the Pt protective layer, AlSiC amorphous film and Si substrate. Figure 2 It can be seen that the AlSiC amorphous film has uniform organization, dense structure and few defects; Figure 3 TEM selected area electron diffraction pattern and high resolution image, Figure 3 It can be seen that the atomic arrangement of the Si matrix is very regular and highly ordered. In contrast, in the AlSiC amorphous film on the surface of the Si matrix, the Al, Si and C atoms do not show the regular atomic arrangement of the Si matrix. Their atomic arrangement is disordered, presenting a completely disordered amorphous structure.
[0051] Figure 4 The loading-unloading curve of the AlSiC amorphous film prepared in this example in nanoindentation. Figure 4 It can be seen that the hardness value of the AlSiC amorphous film prepared in this embodiment is 17.37 GPa, and the Young's modulus is 193.39 GPa.
[0052] Figure 5 The surface morphology of the AlSiC amorphous film prepared in this example after nano-scratching, the load is gradually increased from 0 to 100mN, Figure 5 It can be seen that no cracks or failures occur when the nano scratch load reaches 100 mN, indicating that the AlSiC amorphous film has good toughness and high bonding strength with the substrate.
[0053] Example 3
[0054] The single crystal silicon substrate is fixed on the base plate, and the automatic sample feeder sends the base plate into the magnetron sputtering coating chamber, and the vacuum is evacuated to make the vacuum degree of the vacuum chamber reach 5×10 -4 Pa, argon gas was introduced into the vacuum chamber with a flow rate of 110 sccm, and etching was first performed at a power of 200 W for 30 s, and then at a power of 300 W for 200 s.
[0055] A composite material of Al and SiC (Al: 30 wt.%, SiC: 70 wt.%) was provided as a target material, and a radio frequency power source was used to clean the surface of the target material at a power of 200 W for 30 seconds.
[0056] Then, an AlSiC amorphous film was deposited on a single crystal silicon substrate by a magnetron sputtering method. In the magnetron sputtering step, a radio frequency power supply was used with a power of 500 W, a deposition pressure of 0.32 Pa, a substrate rotation speed of 10 r / min, and a deposition time of 18,000 seconds. After the deposition process, an automatic sampling device took the substrate out of the vacuum chamber to obtain an AlSiC amorphous film with a thickness of 1.8 μm, wherein the atomic proportion of Al in the AlSiC amorphous film was 22.8%, the atomic proportion of Si was 34.7%, and the atomic proportion of C was 42.5%.
[0057] After testing, the hardness value of the AlSiC amorphous film prepared in this embodiment is 16.56 GPa, the Young's modulus is 191.09 GPa, and no cracks appear when the nano scratch load reaches 100 mN.
[0058] Example 4
[0059] The single crystal silicon substrate is fixed on the base plate, and the automatic sample feeder sends the base plate into the magnetron sputtering coating chamber, and the vacuum is evacuated to make the vacuum degree of the vacuum chamber reach 5×10 -4 Pa, argon gas was introduced into the vacuum chamber with a flow rate of 110 sccm, and etching was first performed at a power of 200 W for 30 s, and then at a power of 300 W for 200 s.
[0060] A composite material of Al and SiC (Al: 30 wt.%, SiC: 70 wt.%) was provided as a target material, and a radio frequency power source was used to clean the surface of the target material at a power of 200 W for 30 seconds.
[0061] Then, an AlSiC amorphous film was deposited on a single crystal silicon substrate by a magnetron sputtering method. In the magnetron sputtering step, a radio frequency power supply was used with a power of 550W, a deposition pressure of 0.33Pa, a substrate rotation speed of 10r / min, and a deposition time of 18000 seconds. After the deposition process, an automatic sampling device took the substrate out of the vacuum chamber to obtain an AlSiC amorphous film with a thickness of 1.9μm, wherein the atomic proportion of Al in the AlSiC amorphous film was 21.0%, the atomic proportion of Si was 33.5%, and the atomic proportion of C was 45.5%.
[0062] After testing, the hardness value of the AlSiC amorphous film prepared in this embodiment is 16.94 GPa, the Young's modulus is 192.21 GPa, and no cracks appear when the nano scratch load reaches 100 mN.
[0063] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0064] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An amorphous film, characterized in that: The amorphous film is an AlSiC amorphous film, which is composed of Al, Si and C.
2. The amorphous film according to claim 1, characterized in that: The amorphous film is composed of 20.6%-22.8% Al, 33.1%-34.7% Si and 42.5%-46.3% C in terms of atomic fraction.
3. The amorphous film according to claim 1, characterized in that: The thickness of the amorphous film is 800nm-2μm.
4. A method for preparing an amorphous thin film according to any one of claims 1 to 3, characterized in that: The following steps are involved: Providing target materials; The amorphous film is deposited on the substrate by magnetron sputtering.
5. The method for preparing an amorphous thin film according to claim 4, characterized in that: The target material is selected from a composite material of Al and SiC.
6. The method for preparing an amorphous thin film according to claim 5, characterized in that: In the composite material of Al and SiC, the mass ratio of Al to SiC is 3:
7.
7. The method for preparing an amorphous thin film according to claim 4, characterized in that: In the magnetron sputtering step, the radio frequency power applied during deposition is 500W-600W.
8. The method for preparing an amorphous thin film according to claim 4, characterized in that: In the magnetron sputtering step, the deposition gas pressure is 0.32Pa-0.36Pa.
9. The method for preparing an amorphous thin film according to claim 4, characterized in that: In the magnetron sputtering step, the deposition time is 7200 seconds to 18000 seconds.
10. An amorphous film as claimed in any one of claims 1 to 3 used as a surface protective material.
Citation Information
Patent Citations
Multifunctional Al-doped core-shell structure SiC nanowire and preparation method and application thereof
CN118026731A
Production of silicon carbide single crystal epitaxial wafer
JP2016166101A
ANTIOXIDANT ADDITIVES FOR PRODUCING REFRACTORY PRODUCTS MgO-C AND Al2O3-C
RO126848A0
Method for chemical nickel plating of the surface of a metal-matrix composite material aluminum-silicon carbide
RU2792669C1
Bulk amorphous alloy heat sink
WO2013058754A1
Cited By
Aluminum-plastic film for packaging lithium battery and preparation method of aluminum-plastic film
CN121149531A